The PRESSURE AND TEMPERATURE MONITORING SYSTEM OF ROCKET MOTORCYCLE COMBUSTION BASED ON RASPBERRY PI 4.0 - Prasetiyo, Deden; Minggu, Desyderius; Anwar, Mohamad (Pustaka Poltekad, 2021)
Abstract – Rockets have an important role in today's era because they really help the activities carried out by the Indonesian National Army in order to maintain the integrity of the Unitary Republic of Indonesia. Raspberry pi 4.0 has several advantages and 2 functions, namely as a microprocessor and microcontroller. The monitoring system for the pressure and temperature of the rocket motor combustion chamber is made in such a way by using the red node software so that it can find out real-time data on the pressure and temperature of the resulting rocket motor combustion chamber. The pressure and temperature monitoring system of the rocket motor combustion chamber is equipped with a pressure transducer sensor, temperature sensor and load cell as the rocket load will be maximized by 1 ton. Control data generated from the pressure and temperature of the motor combustion chamber is sent to the raspberry pi via serial communication. This research was conducted based on pure experiments.